Influence of base of support size on arm pointing performance and associated anticipatory postural adjustments - Yiou, Eric; Hamaoui, Alain; Le Bozec, Serge (Neuroscience letters, 2007)
The current study was designed to test the effect of changing the base of support (BoS) size in the initial posture on the performance of a pointing task and the associated “anticipatory postural adjustments” (APAs). Subjects performed series of arm pointing tasks at maximal velocity, from five postures that differed by the antero-posterior (AP) distance between the heels. This distance was increased stepwise from 0 cm (P0 condition) to 40 cm (P40 condition). Kinetics data were collected with a large force-plate, and kinematics data of the pointing were collected with a bi-axial accelerometer (AP and vertical direction) fixed at the wrist. ANOVA showed that the amplitude and the efficiency of the APAs, as well as the performance of the pointing, all statistically increased from P0 to P40 (with 0.0001 < P < 0.01). Altogether, these results provide support to the “Posturo-Kinetic Capacity” theory according to which the performance of the focal component of a motor task tightly depends on the capacity of the postural component to develop efficient anticipatory dynamics.